International Financial Statistics, November 2017. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses annual publication detailed data on transactions in revenue, expense, net acquisition of assets and liabilities, other economic flows, and balances of assets and liabilities of general government and its subsectors. International Financial Statistics (IFS), Balance of Payments Statistics (BOPS), Direction of Trade Statistics (DOTS), and Government Finance Statistics (GFS) are available on DVD-ROM by annual subscription. The DVD-ROMs incorporate a Windows-based browser facility, as well as a flat file of the database in scientific notation. The Statistics Department of the IMF is pleased to make available to users the IFS, Balance of Payments Statistics (BOPS), DOTS, and Government Finance Statistics (GFS) databases through the new, easy-to-use data. In the interest of streamlining and standardizing datasets, all indicator codes have been converted to one code/indicator that is the same in all media.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet